2013
DOI: 10.5817/sp2013-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Looking at two sides of the same coin: phenomenologically oriented vignette research and its implications for teaching and learning

Abstract: This contribution provides insights into learning research conducted at the University of Innsbruck, Austria, where vignette research was developed in a grant-funded project still in progress. It has been designed to gain access to students' learning experiences in the classroom as they occur rather than measuring learning by its outcome. The authors frame the research need out of which this lived experience methodolog y developed and describe its theoretical foundations in phenomenolog y. The vignette researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…It was decided that a second intervention (Phase 2b) would be beneficial. A phenomenologically oriented vignette (Ammann, 2018;Schratz et al, 2013) was written (Table 3). Each sentence of this was an experience of the students elicited during Phase 1 that had been confirmed as important and relevant during Phase 2a.…”
Section: Multiphase Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It was decided that a second intervention (Phase 2b) would be beneficial. A phenomenologically oriented vignette (Ammann, 2018;Schratz et al, 2013) was written (Table 3). Each sentence of this was an experience of the students elicited during Phase 1 that had been confirmed as important and relevant during Phase 2a.…”
Section: Multiphase Designmentioning
confidence: 99%
“…However, many students reported that the imagined Story D lacked authenticity as they simply said they would not go to the theme park, and although the discussion could proceed hypothetically, it was less applicable. It was decided to revert to the students' experiences as the source and write a new phenomenologically oriented vignette (Ammann, 2018;Schratz et al, 2013). This was used for Phase 2b to explore financial decision making in a richer context (Table 3).…”
Section: Phase 2: Interventionmentioning
confidence: 99%
“…In order to explore the phenomena of personal transformation I participated in a six-day Heroine/Hero’s Journey workshop in Germany in 2018. The methodological lens of this research is the phenomenologically oriented vignette research (Peterlini, 2016; Schratz et al, 2013). To describe a phenomenon through the lens of vignette research is to show “how something emerges as something in perception, performance, action, analysis or imagination” (Schratz et al, 2013, p. 60).…”
Section: Phenomenologically Oriented Vignette Researchmentioning
confidence: 99%
“…The methodological lens of this research is the phenomenologically oriented vignette research (Peterlini, 2016; Schratz et al, 2013). To describe a phenomenon through the lens of vignette research is to show “how something emerges as something in perception, performance, action, analysis or imagination” (Schratz et al, 2013, p. 60). In order to be able to pinpoint these direct moments of co-experienced experiences, a sensual and embodied description of that which arises is required.…”
Section: Phenomenologically Oriented Vignette Researchmentioning
confidence: 99%
See 1 more Smart Citation